2008
DOI: 10.1348/014466508x304414
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor trainees' and their supervisors' perceptions of attainment of knowledge and skills: An empirical evaluation of a psychotherapy supervisor training programme

Abstract: Objectives This study aimed to evaluate the success of a two-year, part-time training programme for psychotherapy supervisors. A second aim was to examine factors that might contribute to perceived knowledge and skills attainment during the training course.Design This is a naturalistic, longitudinal study where several measures are used to examine group process and outcome.Methods Supervisor trainees' (n=21) and their facilitators' (n=6) ratings of learning (knowledge and skills), relations to the supervisor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The purpose of this study is to demonstrate that psychotherapy researchers can utilise this training module with various process measures, the CPPS being used as merely one example. These results are consistent with Sundin, Ogren, and Boethius () in that they suggested that directive, active, and structured training is related to greater training benefit and in this case higher reliabilities on process measures.…”
Section: Discussionsupporting
confidence: 90%
“…The purpose of this study is to demonstrate that psychotherapy researchers can utilise this training module with various process measures, the CPPS being used as merely one example. These results are consistent with Sundin, Ogren, and Boethius () in that they suggested that directive, active, and structured training is related to greater training benefit and in this case higher reliabilities on process measures.…”
Section: Discussionsupporting
confidence: 90%
“…In Australia, the Supervisor Training and Accreditation Program (O'Donovan, Dooley, Kavanagh, & Melville, 2009) has resulted in over 1000 psychologist supervisors receiving a 2-day workshop since 2004, with evidence that it is associated with high levels of participant satisfaction (86% endorsement of the workshop, overall) and significant increases in evaluations of knowledge about supervision and the use of a range of supervision methods. From Sweden, Sundin, Ogren, and Boethius (2008) reported on a psychotherapy supervisors' training programme. Although the numbers involved are more modest (e.g.…”
Section: Empirical Evidence To Support Supervisor Training Programmesmentioning
confidence: 99%
“…It is reasonable to assume that he or she was able to assess his or her supervisees fairly well. Because of the paucity of instruments to evaluate group supervision in psychotherapy (for a review, see Sundin, Ö gren, & Boalt Boëthius, 2008), this research uses instruments that are developed specifically for this purpose. The limited knowledge of the instruments' psychometric properties suggests that the results of this study need to be treated carefully.…”
Section: Discussionmentioning
confidence: 99%